Weibull Reliability Modeling with Right-Censored Data and Age-Replacement Optimization for IDG on Boeing 737-900ER - Yoga Yulasmana; Beni Barliansah (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
This paper develops a Weibull-based reliability model for the Integrated Drive Generator (IDG) installed on Boeing 737-900ER aircraft operated in Indonesian low-cost carrier conditions. Time-to-removal is modeled on a Flight Hours (FH) exposure scale and explicitly incorporates right-censored observations using Maximum Likelihood Estimation (MLE). The estimated Weibull shape parameter (?= 3.308 and ? = 7261 FH) indicates a wear-out dominated failure pattern typical of rotating machinery degradation. An age-replacement cost model is then formulated to minimize expected cost rate (USD per FH) by trading planned preventive cost, unplanned corrective cost, and downtime penalties. The Mean Time to Failure (MTTF) is approximately 6514 FH. Cost optimization results suggest an optimal preventive replacement interval in the range of 4750-6650 FH, with a baseline recommendation of approximately 5450 FH. A sensitivity analysis across representative cost scenarios demonstrates how the optimal preventive maintenance interval shifts when operational disruption costs increase. The proposed workflow provides a practically implementable template for maintenance planning of removal-driven line replaceable units under high utilization.